2022
DOI: 10.31219/osf.io/fxtmz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review of deep learning and machine learning for building energy

Abstract: The building energy (BE) management has an essential role in urban sustainability and smart cities. Recently, the novel data science and data-driven technologies have shown significant progress in analyzing the energy consumption and energy demand data sets for a smarter energy management. The machine learning (ML) and deep learning (DL) methods and applications, in particular, have been promising for the advancement of the accurate and high-performance energy models. The present study provides a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Therefore, emotion regulation can be effective on psychological toughness. By Increasing the data points the machine learning methods can be used, e.g., [33][34][35][36][37][38][39][40][41][42][43][44]. Therefore, the study on the perception to life and belief system on self-resilience and psychological toughness of cancer patients about the mediating role of emotion regulation can be better investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, emotion regulation can be effective on psychological toughness. By Increasing the data points the machine learning methods can be used, e.g., [33][34][35][36][37][38][39][40][41][42][43][44]. Therefore, the study on the perception to life and belief system on self-resilience and psychological toughness of cancer patients about the mediating role of emotion regulation can be better investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Data pre-processing includes noise removal and data normalization [21][22][23][24]. First, the data is normalized, then the beginner clustering method is used to identify the outlier data, and removal of the out-of-range data is performed [25][26][27][28][29][30].…”
Section: A Data Preprocessingmentioning
confidence: 99%
“…Another example of using deep networks in the energy sector is to perform the assets management for the electrical grid companies (Kala et al, 2020), where the authors showed that their proposed algorithm involves the faster regional convolutional neural networks outperformed the human-coding efforts for asset management. For a comprehensive review of deep learning for energy systems and building energy, please see, Forootan et al (2022) and Ardabili et al (2022), respectively.…”
Section: Energy Demand/consumption Forecastingmentioning
confidence: 99%